2020
DOI: 10.37496/rbz4920180121
|View full text |Cite
|
Sign up to set email alerts
|

Influence of temperament-related genes on live weight traits of Charolais cows

Abstract: R. Bras. Zootec., 49:e20180121, 2020 https://doi.org/10.37496/rbz4920180121Breeding and genetics Full-length research article Influence of temperament-related genes on live weight traits of Charolais cowsABSTRACT -We investigated whether a panel of molecular markers previously associated with temperament has an effect on live growth traits. Phenotypic data from 412 Charolais cows categorized according to their age in adult and young cows were used to determine Pearson's correlations between birth (BW), weaning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Genetic analysis of the temperament evaluation proves its genetic connection and correlation with other productive features, especially in young animals (Garza-Brenner et al 2020). According to (Riley et al 2016;Costilla et al 2020) the heredity of the temperament is moderate within h 2 = 0.30-0.35.…”
Section: Resultsmentioning
confidence: 95%
“…Genetic analysis of the temperament evaluation proves its genetic connection and correlation with other productive features, especially in young animals (Garza-Brenner et al 2020). According to (Riley et al 2016;Costilla et al 2020) the heredity of the temperament is moderate within h 2 = 0.30-0.35.…”
Section: Resultsmentioning
confidence: 95%
“…Garza-Brenner et al (5) selected a group of 19 genes that participate in the dopamine and serotonin pathway, and through a protein-protein interaction (PPI) analysis, they identified four new interacting candidate genes (POMC, NPY, SLC18A2, and FOSFBJ), of which POMC, SLC18A2 and DRD3, HTR2A (selected based on their function) revealed SNPs associated with Exit Velocity (EV) and Pen Score (PS), which are measurements of bovine temperament in a population of Charolais cattle. The same group found that the variations in these genes (DRD3, HTR2A, and POMC) had an effect on bovine growth (birth weight) in a population of Charolais cattle, showing that the identified variations not only had an effect on bovine temperament but also on live weight traits (6) . Similarly, with the objective of evaluating the potential relationship of two of these SNPs in the DRD3 and HTR2A genes with bovine temperament and growth characteristics, and feed efficiency, a population of Angus, Brangus, and Charolais cattle with temperament assessments was analysed; the results indicated that there was no association with EV and PS, but the SNP in the HTR2A gene was associated with feed efficiency in Brangus cattle (7) .…”
Section: Introductionmentioning
confidence: 94%